The CIA Book Club by Charlie English review – ‘It was like fresh air’ - Simpson, John (The Guardian, 2025)
A fascinating, exciting history of how the agency smuggled subversive books across the iron curtain
United States of America
Keywords: Books; CIA; Culture; History books; Politics books